Sosiaalitilit ja moraalikato - Jukka Lassila; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2009)
Moral hazard means that people with insurance may take greater risks because they know they do not bear the full consequences of their actions. This can occur with both private insurance and social insurance. Deductibles can be used to alleviate the problem. An interesting way to bring deductibles into social insurance is to establish individual social accounts. Mandatory payments into individual social accounts that finance social insurance payments replace taxes that are currently financing social-insurance benefits. At retirement, the remaining balances in the accounts are paid to account holders or added to their retirement benefits. If the account balance is negative at that time, the account is set to zero. The report considers individual unemployment accounts, including severance payments accounts and employment bonuses, and health and long-term care accounts.
Keywords: H53; H55; 330; Social insurance; moral hazard; individual social accounts; Sozialversicherung; Moral Hazard; Sozialversicherungsfinanzierung